Scope and closures - Simpson, Kyle; St. Laurent, Simon; MacDonald, Brian (Sebastopol, CA ; Mumbai : O'Reilly Media ; Shroff Publishers and Distributors Pvt. Ltd., 2015)
This concise yet in-depth guide takes you inside scope and closures, two core concepts you need to know to become a more efficient and effective JavaScript programmer. You'll learn how and why they work, and how an understanding of closures can be a powerful part of your development skillset.
CSE
Hay Trade International
Keywords: Java (Computer program language); Java (Computer program language).; Computer science